Drugs as a cause of perforating dermatoses – a literature review - Mądrzak, Lidia; Staniszewska, Izabela; Moskwa, Arkadiusz; Kalińska-Bienias, Agnieszka (Dermatology Review/Przegląd Dermatologiczny, 2024)
Perforating dermatoses represents a diverse group of skin diseases characterised by extrusion of dermal materials through the skin. Perforating dermatoses are grouped according to the types of eliminated material and clinical features into the following: reactive perforating collagenosis, elastosis perforans serpiginous, perforating folliculitis, and Kyrle’s disease. We conducted a literature review to investigate the associations between perforating dermatoses and drugs. Perforating dermatoses can be induced by the molecularly targeted therapy drugs (sorafenib, nilotinib, dasatinib, erlotinib, gefitinib, vemurafenib, lenvatinib, sirolimus, bevacizumab, necitumumab, panitumumab, cetuximab, bendamustine-rituximab, terepril), monoclonal antibodies (infliximab, etanercept, ranibizumab, natalizumab), as well as immunomodulatory imide drugs (lenalidomide, leflunomide), antiretroviral drugs (indinavir, telaprevir) and penicillamine. Sorafenib is the most common molecularly targeted therapy drug which was described as a cause of perforating dermatoses. The mechanisms responsible for inducing perforating dermatoses with drugs are unknown.